2020
DOI: 10.1111/jfb.14641
|View full text |Cite
|
Sign up to set email alerts
|

Group swimming behaviour and energetics in bluegillLepomis macrochirusand rainbow troutOncorhynchus mykiss

Abstract: Group swimming size influences metabolic energy consumption and swimming behaviour in fishes. Hydrodynamic flows and vortices of other fish are thought to be beneficial in terms of the energetic costs of swimming. Similarly, abiotic obstructions have been shown to have similar benefits with respect to metabolic consumption in swimming fish such as rainbow trout Oncorhynchus mykiss. The current study works to examine metabolic rates and swimming behaviours as a function of group swimming with bluegill sunfish L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Based on (1), (5), and ( 7 Research shows that group swimming affects the metabolic rate of fish and the behavior of the fish while swimming [45]. According to the results, there are significantly more large yellow croakers in the environment with flow velocity below 0.1 m s -1 than the other environments.…”
Section: The Endurance Swimming Model Of Large Yellow Croakermentioning
confidence: 98%
“…Based on (1), (5), and ( 7 Research shows that group swimming affects the metabolic rate of fish and the behavior of the fish while swimming [45]. According to the results, there are significantly more large yellow croakers in the environment with flow velocity below 0.1 m s -1 than the other environments.…”
Section: The Endurance Swimming Model Of Large Yellow Croakermentioning
confidence: 98%
“…Liao and colleagues published a series of papers on rainbow trout Oncorhynchus mykiss (Walbaum 1792) employing entrainment swimming behaviours in association with flow obstructions [2][3][4][5][6]. These behaviours significantly reduced the metabolic cost of swimming in a respiratory swim tunnel when an obstruction is present compared to when the obstruction is absent [7][8][9]. Like entrainment, swimming in groups reduces the energetic cost of locomotion, at least for some fish species [9].…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours significantly reduced the metabolic cost of swimming in a respiratory swim tunnel when an obstruction is present compared to when the obstruction is absent [7][8][9]. Like entrainment, swimming in groups reduces the energetic cost of locomotion, at least for some fish species [9]. Group swimming has been proposed as a mechanism for increasing swimming efficiency, as a swimming fish generates a turbulent wake of eddies similar to that of a flow obstruction [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a minimum number of individuals may be required in order for members to experience the benefits of group living, and this number can vary widely across species. For example, trailing striped surfperch ( Embiotoca lateralis ) in a group of four consumes less oxygen than solitary fish swimming at the same flow rate (Johansen et al., 2010), maximum metabolic rate of bluegill sunfish ( Lepomis macrochirus ) in groups of three is significantly lower than that of individual fish (Currier et al., 2021), and grey mullet ( Liza aurata ) swimming in schools of eight save energy regardless of their spatial position compared to solitary individuals (Marras et al., 2015). Theoretical studies on virtual schools have also suggested that rectangular or diamond shaped‐formations could provide energetic benefits compared to swimming in isolation but require at least four individuals to form the specific group structure (Hemelrijk et al., 2015).…”
Section: Introductionmentioning
confidence: 99%